(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Objective: To identify the spectrum of adolescent female genital tract anomaly in a tertiary level hospital. Methodology: It was a cross-sectional descriptive study conducted in the Obstetrics & Gynaecology department of Mymensingh Medical College Hospital over six months from October 2019 to April 2020. Here, 30 adolescent females with genital tract anomalies were selected after fulfilling the inclusion criteria by a non-random purposive sampling. The common variants of genital tract anomaly were identified. Associated renal anomaly was also detected. Statistical analysis was done by using SPSS V21.0. Results: Among 30 patients, majority (20) were in the early adolescent group (10-14 years) and unmarried (83.3%). The presenting complaints varied from non-establishment of menstruation in most (70%) of the cases to cyclic pelvic pain and severe lower abdominal pain (56.7%), progressive pelvic lump (23.3%), dysmenorrhea (20%) and difficulty in sexual intercourse (16.7%) in other cases. The spectrum of genital tract anomalies was found to be imperforate hymen (36.7%), cribriform hymen (10%), mullerian agenesis (30.0%), transverse vaginal septum (6.7%) etc. The ultimate mode of diagnosis was mainly clinical in 16 patients (53.3%) and ultrasonography of whole abdomen in 30% of cases. Associated renal anomaly was found in 6 cases (20%). The management approach was surgical in 20 (66.7%) patients with additional counselling. Conclusion: Adolescent female genital tract anomalies commonly become evident around puberty, mostly with menstrual problems and cause a variety of symptoms. Hence, their comprehensive understanding and thorough evaluation are of utmost importance. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 63-68